Majlis dar qiṣṣa-yi rasūl (ṣalawāt Allāh ʿalayhi) - Pārsānasab, Muḥammad, (Miras Maktoob, ISBN: 9789004365452., 2019)
In Persian literature, so-called ' majālis ' works typically evoke the atmosphere of a religious gathering. In such a gathering, a chronicler relates parts of the history of Islam and the lives and times of its prominent representatives, often referring to trustworthy sources. Besides, questions may be asked, while teachings or sermons may also be given. Examples are Jalāl al-Dīn Rūmī's (d. 672/1273) Majālis-i sabʿa and Saʿdī's (d. 691/1292) Majālis-i panj-gānah . Judging by its title, the present work by an unknown author from the 5th/12th century-it is not known if it was originally written in Persian or translated from Arabic-would seem to belong to this same type of writings. Only, on closer inspection this is not the case. Being mostly inspired by Ibn Isḥāq's (d. 150/767) al-Sīra al-nabawiyya and Abū Ḥātim al-Rāzī's (d. 322/933-4) Aʿlām al-nubuwwa , only its last five chapters are called majlis , but then lack the characteristics of a typical majālis work.